Non-enzymatic, template-directed ligation of 2'-5' oligoribonucleotides. Joining of a template and a ligator strand. - Sawai, H (1998)
Decauridylate containing exclusively a 2'-5' phospho-diester bond ([2'-5']U10) served as a template for the synthesis of oligoadenylates [oligo(A)s] from the 5'-phosphorimidazolide of 2'-5' diadenylate (ImpA-2'p5'A). Joining of [2'-5']U10and ImpA2'p5'A also took place in substantial amounts to yield long-chain oligoribonucleotides in the template-directed reaction. An unusual CD spectrum ascribed to helix formation between [2'-5']U10and [2'-5'](pA)2was observed under the same conditions as that of the template-directed reaction. The 3'-5' linked decauridylate ([3'-5']U10) also promoted the template-directed synthesis of oligo(A)s from ImpA2'p5'A, but more slowly compared with [2'-5']U10. The results indicate that short-chain RNA oligomers with a 2'-5' phosphodiester bond could lead to longer oligoribonucleotides by template-directed chain elongation.